Implementasi Metode Behavioural Scoring untuk Perancangan Sistem Penilaian Pembayaran Kredit Konsumen - Hurnaningsih, Hurnaningsih; Julisawati, Elly Agustina (Teknik Informatika Universitas Pamulang, 2021)
PT. Sinar Indo Lestari is a company engaged in real estate development that has problems on its customer’s payment management specifically its sales department admin. Some of the encountered problems are Difficulty in finding customers whose payments are already overdue, inability to easily view Accounts Receivable value of customer’s down payment, difficulty in policy making, manual inputs are still required to build Accounts Receivable reports. Methods that approach problems in payment use Behavioral Scoring method approach. This method will help in decision making that payment punctuality of a customer is going to have an impact on 'cash bertahap' policy that will be given. 'Cash bertahap' policy will be given through performance score throughout customers' down payment period.